Synthesis and characterization of centrifugally cast composites - Ng, Siew Sing. (2008)
The development of new materials through intensive research is in response to the rapidly changing and highly competitive manufacturing environment. Companies must be able to produce innovative and quality products in order to capture a greater proportion of the market share in order to out-perform their competitors.